Analysis of Tuna Fish Sales Price on Employee Family Income During the Covid 19 Pandemic Limited Liability Company Sinar Pure Food International Bitung City - Alzefin YRM Sinolungan; Rahel Widiawati Kimbal; Arie Frits Kawulur (AIBPM Publisher, 2022)
The purpose of the study was to analyse and explain the application of tuna sales price analysis in determining optimal family income and achieving the desired profit during the Covid 19 Pandemic at the Sinar Pure Foods International Limited Company, Bitung City. This type of research is descriptive with a quantitative approach. Data collection techniques are interviews, documentation, and questionnaires. Research variables: (1). Independent Variable(X): Tuna Fish Sales Price; (2). Bound Variable (Y): Employee's Family Income. Purposive Sampling Sampling technique. Population 60 people with sample 37 people. Data processing technique with Simple Linear Regression Analysis: Y= a+bX. From the results of the study, it was found that there was a positive relationship between variable X, namely the selling price of tuna and variable Y, the income of the employee's family was positive. So, the price goes up which causes the family income to increase. So, there is a significant relationship between the selling price of tuna and the income of the employee's family during the covid 19 pandemic.Keywords: Price, Employee, Family income, Company, Covid 19.